2015
DOI: 10.1016/j.neuropharm.2014.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Differences between magnetoencephalographic (MEG) spectral profiles of drugs acting on GABA at synaptic and extrasynaptic sites: A study in healthy volunteers

Abstract: A range of medications target different aspects of the GABA system; understanding their effects is important to inform further drug development. Effects on the waking EEG comparing these mechanisms have not been reported; in this study we compare the effects on resting MEG spectra of the benzodiazepine receptor agonist zolpidem, the delta sub-unit selective agonist gaboxadol (also known as THIP) and the GABA reuptake inhibitor tiagabine. These were two randomised, single-blind, placebo-controlled, crossover st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 49 publications
6
35
0
Order By: Relevance
“…However, this can be largely excluded as one previous study found significant effects on TMS‐EMG measures with the same dose (15 mg; Werhahn et al, ). Furthermore, we found that TGB strongly increased preTMS EEG power in all frequency bands (Figure and Supporting Information Figure S3), confirming findings of two resting‐state magnetoencephalographic studies (Muthukumaraswamy & Liley, ; Nutt et al, ) and, therefore, indicating a significant effect of TGB on brain activity in the present experiments.…”
Section: Discussionsupporting
confidence: 91%
“…However, this can be largely excluded as one previous study found significant effects on TMS‐EMG measures with the same dose (15 mg; Werhahn et al, ). Furthermore, we found that TGB strongly increased preTMS EEG power in all frequency bands (Figure and Supporting Information Figure S3), confirming findings of two resting‐state magnetoencephalographic studies (Muthukumaraswamy & Liley, ; Nutt et al, ) and, therefore, indicating a significant effect of TGB on brain activity in the present experiments.…”
Section: Discussionsupporting
confidence: 91%
“…For an overview of the respective MEG acquisition and preprocessing procedures for the psychedelic compounds, see Schartner et al (2017). Full details are given in Carhart-Harris et al (2016) [LSD], Muthukumaraswamy et al (2013) [PSI], Muthukumaraswamy et al (2015b) [KET], and Nutt et al (2015) [TGB]. The MEG data were source-localised to 90 cortical regions according to the standard Automated Anatomical Labelling (AAL) brain atlas (Tzourio-Mazoyer et al, 2002).…”
Section: Experimental Procedure Data Acquisition and Preprocessingmentioning
confidence: 99%
“…us, looking at large-scale MEG resting state networks may give us an insight into the functional organisation of the injured brain and the effects of various drugs on it. It has been shown that MEG can pick up changes in GABA function in the brain and that zolpidem has an influence on changes in GABA action [17]. is makes the analysis of resting state brain oscillations using MEG particularly relevant to understanding the effects of zolpidem.…”
Section: Introductionmentioning
confidence: 99%